A systematic search and assessment of the quality and characterisation of free mobile applications targeting knee pain. (3rd September 2022) - Nogueira, Francisco M. F.; Martins, Ricardo P.; Nery, Ellen C. H. Pereira; Silva, Anabela G.
Abstract: Knee pain has an incidence of approximately 25% in adults and its prevalence has been increasing in the last 20 years. The use of smartphones and mobile applications (apps) has also increased in the 'Health and Fitness' field, which might be a useful complement in the rehabilitation process of these patients. However, it is necessary to investigate the quality of these mobile applications. Aim: This study aimed to assess free mobile apps targeting knee pain and to characterise and critically analyse the interventions described in them. Methods: A systematic search was performed in the Apple store, Play Store and Microsoft Store. Results: A total of 26 applications met the inclusion criteria and were evaluated using the Mobile Apps Rating Scale (MARS), and for their content against guidelines on knee pain intervention. The mean MARS total score was 3.3 (±0.5) and the mean subjective quality score was 2.1 (±0.9) out of a maximum of 5 points each. Most apps combined different types of exercises 88% and included both exercise and pain education (62%). Results: These results suggest a need to improve the quality of these apps aiming to create more engagement and improve app usage. Additionally, as health apps may be useful in pain management and be an alternative to complement rehabilitation, the involvement of health professionals is important during the development process of the apps including evidence‐based content and progression recommendations.